Primary Stenting in a Young Adult with Aortic Coarctation - Salgado, Victor; Martínez-Toro, José; Rodríguez, Edwin (Puerto Rico Health Sciences Journal, 2006)
ABSTRACT: A young male adult with significant aortic coarctation was initially referred to our clinics due to uncontrolled blood pressures. On evaluation the diagnosis of aortic coarctation was evident and confirmed with Magnetic Resonance Angiography (MRA). After discussing treatment options with the patient and his parents they opted for the least invasive procedure possible. Primary stenting of a simple discrete aortic coarctation was performed successfully. The following is a report on the methods used and immediate results.